A new species and a new record of Phanera (Fabaceae) in Laos, with a lectotypification and a new combination for P. involucrans - Yamamoto, Takenori; Souladeth, Phetlasy; Soutakone, Khammon; Kongxaisavath, Deuanta; Tagane, Shuichiro (Phytotaxa, 2024)
A new species of Phanera (Fabaceae), P. roseoalba from the Bolaven Plateau, southern Laos, is described and illustrated, along with its vernacular name and preliminary conservation status. In addition, a distribution of P. nervosa is recorded in Laos for the first time, and a second-step lectotypification is made for Bauhinia involucrans, with a proposal of its new combination P. involucrans.